Dye-Sensitized Solar Cell (DSSC) with TiO2-Cu and Natural Pigmented Dye - Hardeli, Hardeli; Sanjaya, Hary; Novita, Indri Panca; Luli, Rahmaneta; Yunita, Lasmi; Agdisti, Nurul Fadilah; Permatasari, Putri (Universitas Andalas, 2026)
Dye-Sensitized Solar Cells (DSSC) are solar cells that use dye as a sensitizer. Titanium dioxide (TiO2) is a semiconductor that is frequently used in DSSC. However, the effectiveness of TiO2 can decrease due to electron and hole recombination. In this study, copper metal (Cu) was electrodeposited onto the TiO2 layer, where Cu plays a role in forming a barrier layer to reduce electron recombination. Anthocyanins are natural dyes with a broad light spectrum that can be used as a photon absorber in the DSSC. Anthocyanins in this study were extracted from red grape skin (Vitis Vinifera), jengkol skin (Pithecellobium jiringa), senduduk fruit (Melastoma malabathricum L), and mangosteen peel (Garcinia Mangostana L). To create a more stable organic dye, the dye is co-pigmented with salicylic acid. The XRD characterization of the layers revealed a diffraction pattern indicating the presence of anatase-phased and size reduction on TiO2-Cu layers. As a result, the DSSC performance increased. SEM-EDS analysis was performed to determine surface morphology and identify Cu metal. FTIR analysis of dyes revealed the presence of specific anthocyanin groups. The UV-Vis characterization revealed the effect of co-pigmentation on the dye absorption area. The highest DSSC performance with TiO2-Cu coating and co-pigmented dye was achieved in the DSSC by electrodepositing Cu on the TiO2 layer while using grape skin as a dye source.